1997
DOI: 10.1016/s0014-5793(96)01538-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hyaluronate metabolism by progesterone in cultured fibroblasts from the human uterine cervix

Abstract: These results suggest that in cultured fibroblasts from the human uterine cervix progesterone converts hyaluronate metabolism from the synthesis phase to the degradation phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…P inhibits matrix metalloproteinase (MMP) activities (Imada et al, 1997;Sato et al, 1991) and stimulates tissue inhibitor of metalloproteinase (TIMP)-2 in rabbit uterine cervical fibroblasts ; thus, it is considered to also exert a potent inhibitory action on cervical ripening. Our previous results have shown that P suppresses hyaluronate synthesis in human uterine cervical fibroblasts (Tanaka et al, 1994(Tanaka et al, , 1997. One of the principle components of the uterine cervix is PGs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…P inhibits matrix metalloproteinase (MMP) activities (Imada et al, 1997;Sato et al, 1991) and stimulates tissue inhibitor of metalloproteinase (TIMP)-2 in rabbit uterine cervical fibroblasts ; thus, it is considered to also exert a potent inhibitory action on cervical ripening. Our previous results have shown that P suppresses hyaluronate synthesis in human uterine cervical fibroblasts (Tanaka et al, 1994(Tanaka et al, , 1997. One of the principle components of the uterine cervix is PGs.…”
Section: Discussionmentioning
confidence: 93%
“…Although further studies are needed to evaluate the effectiveness of each method, it has been reported that P is promising because the hormone can inhibit prostaglandin production and reduce myometrial contractility, thus maintaining uterine quiescence. We have shown that P suppresses hyaluronate synthesis in human uterine cervical fibroblasts (Tanaka et al, 1994(Tanaka et al, , 1997. Hyaluronate is an extracellular matrix and has been shown to increase prior to parturition in the human uterine cervix, and is thus considered to play an important role in cervical ripening (Osmers et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Gel-filtration HPLC of hyaluronic acid was carried out as described previously (5). The reaction product of cell-free synthesis was applied to a Shodex OHpak KB-805 column (8.0 mm inner diameter x 30 cm; Showa Denko, Tokyo, Japan).…”
Section: Introductionmentioning
confidence: 99%
“…P 4 is essential in pregnancy, and high levels of this hormone are maintained during gestation (Hardy et al 2006). Cervical remodelling during pregnancy depends on P 4 because it can modulate the expression of some components of the extracellular matrix (ECM), thus inhibiting hyaluronate expression (Tanaka et al 1994(Tanaka et al , 1997 and increasing collagenase, elastase and metalloproteinase levels (Andersson et al 2008). Because the cervical tissue mechanical properties are related to the ECM (Myers et al 2008) and because the ECM is the major component of cervical tissue (Leppert 1995), cervical softening is associated with decreased collagen organisation, which is characterised by increased collagen solubility and decreased collagen concentration.…”
Section: Discussionmentioning
confidence: 99%